2022
DOI: 10.1155/2022/1099005
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Midostaurin-Associated Sweet’s Syndrome

Abstract: Acute febrile neutrophilic dermatosis which is referred as Sweet’s syndrome (SS) is a dermatological condition characterized by fever, erythematous rash, and leukocytosis. SS can be idiopathic or associated with malignancies or medications. We present a rare case of SS which developed shortly after starting midostaurin in a patient with acute myelogenous leukemia (AML).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
(31 reference statements)
0
0
0
Order By: Relevance
“…In the pivotal trial that led to approval of midostaurin, there were no reported cases of DS occurring in patients using midostaurin and, to our knowledge, there have been no cases of DS attributed to midostaurin reported in the literature [82]. However, there have been case reports of AFND/Sweet's Syndrome associated with the use of midostaurin in the literature that have resolved with corticosteroid treatment [92,93]. AFND/Sweet's syndrome has been described with other FLT3 inhibitors previously as a manifestation of terminal differentiation of FLT3-mutated blasts [94][95][96].…”
Section: Flt3 Inhibitorsmentioning
confidence: 99%
“…In the pivotal trial that led to approval of midostaurin, there were no reported cases of DS occurring in patients using midostaurin and, to our knowledge, there have been no cases of DS attributed to midostaurin reported in the literature [82]. However, there have been case reports of AFND/Sweet's Syndrome associated with the use of midostaurin in the literature that have resolved with corticosteroid treatment [92,93]. AFND/Sweet's syndrome has been described with other FLT3 inhibitors previously as a manifestation of terminal differentiation of FLT3-mutated blasts [94][95][96].…”
Section: Flt3 Inhibitorsmentioning
confidence: 99%